The Effect of the Grammar Translation Method and the M.U.R.D.E.R Technique in Teaching Reading on the Reading Achievement of Eleventh Grade Students of Senior High School - Elvina Ariyanto (Widya Mandala Surabaya Catholic University, 2008)
The objective of this study is to find out which techniques affect the students’ reading achievement better. The students’ reading achievement is also specified in three types of reading questions; factual, inference, and main idea questions. In this study, the writer used two classes of the eleventh grade belonging to the school year of 2005-2006 as the subject of the study. The writer also developed a research instrument which contains 20 objective items in the form of multiple choices. Each item has four options with one correct answer. After three meetings of treatment, the writer administered a post test to both classes. Having collected the data, the writer analyzed the mean scores of post test using t-test for independent samples at .05 level of significance and 75 degrees of freedom. The result showed that the students taught by using translation technique have better reading achievement than those taught by M.U.R.D.E.R technique.